PREVALENCE OF VARIOUS HEMOGLOBINOPATHIES USING HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY (HPLC): A RETROSPECTIVE CROSS SECTIONAL INSTITUTIONAL STUDY (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Hemoglobinopathies are widely used in the world and form an important health burden to the population in India especially in the northeastern part where HbE and b-thalassemia are very common. “High- performance liquid chromatography (HPLC)” is a dependable and effective reference “tool of screening and” characterizing hemoglobin variants. Objectives: The aim of the study was to find the prevalence and the distribution of different hemoglobinopathies” through HPLC in a tertiary care center and to evaluate the demographic and hematological profile of hemoglobinopathies. Materials and Methods: This was a retrospective cross-sectional study done in the Department of Pathology, Dhubri Medical College, and” a time span of one year. There were 237 patients with hemoglobin variant analysis carried out using HPLC. The laboratory records provided demographic information, hematological parameters and the HPLC results. Cases were grouped into b-thalassemia trait (BTT), HbE trait, HbE disease, compound heterozygous conditions, sickle cell trait (SCT), borderline findings, Hb Lepore trait and normal phenotypes. The analysis was done using descriptive statistics. Results: Among 237 cases (138 (58.2) were abnormal hemoglobins and 99 (41.8) were normal. The women formed 58.6 percent and men 41.3 percent. The abnormality that occurred most frequently was HbE trait (19.8%), with b-thalassemia trait (12.2%), HbE disease (8.9%), borderline results (11.0%), and compound heterozygous states (5.1%). One sickle cell trait (0.4) and two Hb Lepore trait (0.8) were detected. Most of the cases were in the age bracket of 21- 30 years.” The distribution based on community was more prevalent in Muslims (53.1) than in Hindus (46.8). Almost 45.5 percent of the patients were found to have a hemoglobin level that was less than 7 g/dL which means that there was a high level of anemia in the study population. Conclusion: Hemoglobinopathies are very common among the population under study and HbE related disorders are the most common one. HPLC is a useful screening technique used in the early detection and classification of hemoglobinopathies. Premarital and antenatal screening is suggested to help reduce the burden of diseases in Northeast India by means of regional screening programs.